Old Age and Poverty in Poland, 1945-1989: The Status Regarding Knowledge And Research Problems - Jarosz, Dariusz (Studia Historiae Oeconomicae, 2014)
The history of old age has only relatively recently become explored as a research topic in Poland. This sketch focuses on the relationship between old age and poverty in People’s Republic of Poland. Old age, however, was a significant object of interest of the PRL authorities in at least two aspects. The first was the social security system, particularly in relation to old age and disability pensions, and the second, social care for the aged.